Application of building solid waste mixed asphalt macadam as pavement base material and preparation of building solid waste mixed asphalt macadam
By mixing construction solid waste and molybdenum ore powder with asphalt, high strength, wear resistance and high stability pavement base materials are prepared, which solves the problem of low utilization rate of construction solid waste and molybdenum ore powder and realizes pavement base Performance improvement and environmentally friendly resource utilization.
Patent Information
- Application Number
- CN202411405356.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, construction solid waste is less used in asphalt road projects, especially in flexible base layers of large-particle asphalt gravel pavement, and the comprehensive utilization rate of molybdenum ore waste powder is low, resulting in environmental pollution and waste of resources.
By mixing construction solid waste and molybdenum ore powder with asphalt, building solid waste mixed large-particle asphalt gravel as pavement flexible base material is prepared, and drying and mixing is carried out using specific ratios and processes to form high-strength and wear-resistant and high stability of pavement base materials.
It improves the compressive strength, wear resistance and high temperature stability of pavement base materials, extends the service life of the road, reduces maintenance costs, and effectively utilizes construction solid waste and molybdenum ore powder resources.
Smart Images

Figure CN119219362A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the fields of highway pavement material technology and highway pavement engineering technology, and in particular to the application and preparation of construction solid waste mixed with asphalt macadam as a pavement base material. Background Art
[0002] With the acceleration of industrialization and urbanization, the construction industry has ushered in rapid development, and with it a significant increase in construction solid waste. These untreated construction solid wastes not only occupy a large amount of land resources, but also cause serious impacts on air quality due to the dust generated during transportation and stacking. At the same time, economic growth and modernization have led to the rapid development of transportation infrastructure construction. The huge demand for sand and gravel resources in this process, if met by excessive mining, will cause inestimable damage to the ecological environment. Therefore, recycling and reusing construction solid waste in transportation infrastructure construction can not only effectively reduce environmental pressure, but also be an effective way to promote the implementation of sustainable development strategies.
[0003] In addition, the current amount of molybdenum ore waste powder is huge, but the comprehensive utilization rate is low. A large amount of waste powder accumulates and occupies land, and the harmful substances in it may pollute the soil, water sources and atmosphere, posing a threat to the ecological environment. The "Technical Specifications for the Utilization of Construction Waste in Highway Engineering" (JTG / T 2321-2021) stipulates that construction waste recycled materials can be used for base layers, subbase layers, roadbed filling, foundation treatment and other parts of various grades of highways. Flexible base layers have the advantages of fatigue resistance and anti-reflective cracking. Flexible base layers have obvious advantages in areas with heavy traffic loads, poor roadbed conditions and high environmental protection requirements. However, the current research on the application of construction solid waste in asphalt road engineering is mostly focused on the surface layer or roadbed, and less research on its application in the flexible base layer of large-size asphalt macadam pavement.
[0004] In order to fill the above-mentioned deficiencies, reduce the exploitation of natural sand and gravel resources, increase the utilization rate of construction solid waste and molybdenum ore powder, and meet the performance of flexible pavement base, this scheme proposes a material design of construction solid waste mixed with large-size asphalt gravel as a flexible pavement base, as well as its preparation process and application.
[0005] The present invention provides a method for preparing large-diameter asphalt crushed stone mixed with construction solid waste, in which a small amount of molybdenum ore powder is used to replace mineral powder, and construction solid waste aggregate is used to replace crushed stone aggregate and mixed with asphalt as a flexible base layer of a road surface; and a series of processes capable of applying construction solid waste to a flexible base layer of a road surface to increase the utilization rate of the construction solid waste, while meeting the road performance of the base layer, thereby meeting such practical application needs. Summary of the invention
[0006] In view of this, the purpose of the present invention is to propose an application and preparation of construction solid waste mixed asphalt macadam as a road base material which is reliable and can realize the resource utilization of molybdenum ore powder and construction solid waste.
[0007] In order to achieve the above technical objectives, the technical solution adopted by the present invention is:
[0008] Application of construction solid waste mixed with asphalt macadam as a road base material, the road base material comprising components in parts by weight:
[0009]
[0010] As a possible implementation, further, the limestone aggregate described in this solution has a particle size of less than 37.5 mm. That is, the base material of this solution uses construction solid waste mixed with large-size asphalt crushed stone ATB-30, and its coarse aggregate has a maximum nominal particle size of 37.5 mm limestone crushed stone.
[0011] As a possible implementation mode, further, the construction solid waste described in this scheme includes recycled concrete aggregate and recycled concrete powder, the particle size of the recycled concrete aggregate is 5-20mm; the recycled construction powder is obtained by grinding the building materials, drying the moisture in an oven and sieving through a 0.075mm sieve.
[0012] As a preferred embodiment, preferably, the pavement base material of this solution includes the following components in parts by weight:
[0013]
[0014] As a preferred implementation mode, preferably, the limestone aggregate described in this scheme includes 19.20 parts of aggregate with a nominal particle size of 0-3mm; 10.57 parts of aggregate with a nominal particle size of 3-5mm; 5.00 parts of aggregate with a nominal particle size of 5-10mm; 6.91 parts of aggregate with a nominal particle size of 10-20mm; 34.63 parts of aggregate with a nominal particle size of 20-37.5mm; the construction solid waste includes 7.51 parts of aggregate with a nominal particle size of 5-10mm; and 10.36 parts of aggregate with a nominal particle size of 10-20mm.
[0015] Based on the above, this solution also provides a method for preparing construction solid waste mixed with asphalt gravel as a road base material, which includes:
[0016] Weigh each raw material according to the weight ratio of the pavement base material, and then place it in an oven at 105°C±5°C for 4-6 hours;
[0017] Place limestone aggregate and coarse and fine aggregate of construction solid waste in a mixer and mix them properly with a shovel, then add 70# matrix asphalt and mix for 1-1.5 minutes; then stop mixing, add mineral powder and molybdenum mineral powder and continue mixing until uniform, the total mixing time is 3 minutes, and obtain asphalt mixture;
[0018] The mixed asphalt mixture is poured into a heated mold for molding to obtain the pavement base material.
[0019] By adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:
[0020] 1. Molybdenum ore waste powder is added to the material components of this scheme. It has high strength and wear resistance, which helps to enhance the compressive strength and wear resistance of asphalt mixture. At the same time, the high melting point and good thermal conductivity can improve the stability of asphalt mixture in high temperature environment and reduce the road deformation caused by high temperature environment.
[0021] 2. The cement mortar remaining in the construction solid waste added to the material components of this scheme makes its surface texture abnormally rough, which is conducive to better interaction between aggregate particles and higher surface friction; the rough surface makes its specific surface area significantly higher than that of natural aggregate, greatly improving its efficiency in absorbing water or asphalt; the composition of construction solid waste is complex, and its surface has cement hydration products including CSH (calcium silicate hydrate) and Ca(OH)2. These components have certain activity and can induce chemical reactions with acid asphalt.
[0022] 3. Experiments have shown that the flexible base material produced by this scheme exhibits good stability in high temperature and water environments, and the durability of the material is significantly improved, which can extend the service life of the road and reduce maintenance costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0024] Figure 1 It is the synthetic gradation curve diagram of the mineral material of Example 1-6;
[0025] Figure 2 A schematic diagram of a rutting test of an asphalt mixture test block prepared in Example 4 of the present invention;
[0026] Figure 3 Schematic diagram of the Marshall test of immersion of asphalt mixture test block prepared in Example 4 of the present invention;
[0027] Figure 4 It is a schematic cross-sectional view of a low-temperature splitting experiment of an asphalt mixture test block prepared in Example 4 of the present invention;
[0028] Figure 5 Schematic diagram of a three-point bending fatigue test of an asphalt mixture specimen prepared in Example 4 of the present invention. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention. Similarly, the following examples are only partial embodiments of the present invention rather than all embodiments, and all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0030] This solution provides an application of construction solid waste mixed with asphalt gravel as a road base material, and the road base material includes the following components in parts by weight:
[0031]
[0032] The limestone aggregate described in this scheme has a particle size of less than 37.5 mm.
[0033] The construction solid waste described in this scheme includes recycled concrete aggregate and recycled concrete powder. The particle size of the recycled concrete aggregate is 5-20mm; the recycled construction powder is obtained by grinding the construction materials, drying the moisture in an oven and sieving through a 0.075mm sieve.
[0034] Based on the above, this solution also provides a method for preparing construction solid waste mixed with asphalt gravel as a road base material, which includes:
[0035] (1) Weighing each raw material according to the weight ratio of the pavement base material, and then placing it in an oven at 105°C±5°C for drying for 4-6 hours; then placing the limestone aggregate and the coarse and fine aggregates of the construction solid waste in a mixer and mixing them appropriately with a shovel, and then adding 70# matrix asphalt to mix for 1-1.5 minutes; then pausing the mixing, and then adding the mineral powder and molybdenum mineral powder and continuing to mix until uniform, the total mixing time is 3 minutes, and obtaining an asphalt mixture;
[0036] (2) pouring the mixed asphalt mixture into a heated mold to form the pavement base material, wherein the forming is guided by the relevant provisions of JTG E20-2011.
[0037] In order to further explain this solution, the material formulas of 6 groups of embodiments are compared as follows:
[0038] Table 1 Raw material ratio
[0039]
[0040] Among them, Examples 1-6 respectively represent asphalt mixtures in which the replacement rate of construction solid waste in 5-10mm and 10-20mm aggregates is 0%, 20%, 40%, 60%, 80% and 100%.
[0041] Figure 1 The synthetic gradation curve of the mineral material of Example 1-6 is used to determine the optimal asphalt-stone ratio by the rotary compaction method. According to the rotary compaction parameter research, it is finally determined that the instrument parameters are set to: vertical pressure 600kPa, rotation angle 1.25°, rotation rate 30r / min, initial compaction times Nini is 8 times, design compaction times Ndes is 100 times, and maximum compaction times Nmax is 160 times. The asphalt-stone ratios of the asphalt mixtures obtained in Example 1-6 when the void ratio is 4% under the design rotary compaction times are 3.0%, 3.1%, 3.2%, 3.3%, 3.5%, and 3.6%, respectively.
[0042] In Table 1, the limestone aggregate of Example 1 is 94.39 parts, of which the aggregate with a nominal particle size of 0-3 mm is 19.29 parts; the aggregate with a nominal particle size of 3-5 mm is 10.55 parts; the aggregate with a nominal particle size of 5-10 mm is 12.55 parts; the aggregate with a nominal particle size of 10-20 mm is 17.30 parts; the aggregate with a nominal particle size of 20-37.5 mm is 34.70 parts; and the construction solid waste is 0 parts.
[0043] The limestone aggregate in Example 2 is 88.28 parts, of which 19.27 parts are aggregates with a nominal particle size of 0-3 mm; 10.55 parts are aggregates with a nominal particle size of 3-5 mm; 9.97 parts are aggregates with a nominal particle size of 5-10 mm; 13.88 parts are aggregates with a nominal particle size of 10-20 mm; 34.61 parts are aggregates with a nominal particle size of 20-37.5 mm; and 5.96 parts are construction solid waste, of which 2.49 parts are aggregates with a nominal particle size of 5-10 mm; and 3.47 parts are aggregates with a nominal particle size of 10-20 mm.
[0044] The limestone aggregate in Example 3 is 82.39 parts, of which 19.25 parts are aggregates with a nominal particle size of 0-3 mm; 10.59 parts are aggregates with a nominal particle size of 3-5 mm; 7.51 parts are aggregates with a nominal particle size of 5-10 mm; 10.39 parts are aggregates with a nominal particle size of 10-20 mm; 34.65 parts are aggregates with a nominal particle size of 20-37.5 mm; and 11.93 parts are construction solid waste, of which 5.00 parts are aggregates with a nominal particle size of 5-10 mm; and 6.93 parts are aggregates with a nominal particle size of 10-20 mm.
[0045] The limestone aggregate in Example 4 is 76.31 parts, of which 19.20 parts are aggregates with a nominal particle size of 0-3 mm; 10.57 parts are aggregates with a nominal particle size of 3-5 mm; 5.00 parts are aggregates with a nominal particle size of 5-10 mm; 6.91 parts are aggregates with a nominal particle size of 10-20 mm; 34.63 parts are aggregates with a nominal particle size of 20-37.5 mm; and 17.87 parts are construction solid waste, of which 7.51 parts are aggregates with a nominal particle size of 5-10 mm; and 10.36 parts are aggregates with a nominal particle size of 10-20 mm.
[0046] The limestone aggregate in Example 5 is 70.45 parts, of which 19.28 parts are aggregates with a nominal particle size of 0-3 mm; 10.57 parts are aggregates with a nominal particle size of 3-5 mm; 2.50 parts are aggregates with a nominal particle size of 5-10 mm; 3.46 parts are aggregates with a nominal particle size of 10-20 mm; 34.64 parts are aggregates with a nominal particle size of 20-37.5 mm; and 23.87 parts are construction solid waste, of which 10.02 parts are aggregates with a nominal particle size of 5-10 mm; and 13.85 parts are aggregates with a nominal particle size of 10-20 mm.
[0047] The limestone aggregate in Example 6 is 64.49 parts, of which 19.28 parts are aggregates with a nominal particle size of 0-3 mm; 10.57 parts are aggregates with a nominal particle size of 3-5 mm; 0 parts are aggregates with a nominal particle size of 5-10 mm; 0 parts are aggregates with a nominal particle size of 10-20 mm; 34.64 parts are aggregates with a nominal particle size of 20-37.5 mm; and 29.84 parts are construction solid waste, of which 12.52 parts are aggregates with a nominal particle size of 5-10 mm; and 17.32 parts are aggregates with a nominal particle size of 10-20 mm.
[0048] Correspondingly, the processing method of Examples 1-6 includes: weighing the raw materials according to the raw material ratio in Table 1, placing them in an oven at 105°C ± 5°C for drying for 5 hours, then placing the coarse and fine aggregates in a mixer and mixing them appropriately with a shovel, adding asphalt, and mixing for 1-1.5 minutes; pausing the mixing, adding the mineral powder and molybdenum mineral powder and continuing to mix until uniform; the total mixing time is 3 minutes; obtaining a mixture of flexible base materials synthesized from solid waste; then pouring the mixture into a mold for molding, taking the mixture out of the mold after 24 hours, and testing high temperature stability, low temperature crack resistance, water stability and fatigue performance. According to JTG E20-2011 molding and testing, high temperature stability is characterized by dynamic stability (times / mm); low temperature crack resistance is characterized by splitting tensile strength (Mpa), breaking tensile strain, and breaking stiffness modulus (Mpa); water stability is characterized by residual stability (%); fatigue performance is characterized by fatigue life (times), and the test results are shown in Table 2 below:
[0049] Table 2 Raw material ratio and test results
[0050]
[0051] As can be seen from the above table, the asphalt mixtures prepared in Examples 1-6 all meet the requirements of the flexible base for high temperature stability, low temperature crack resistance, water stability and fatigue performance. Among them, Example 4 has the highest dynamic stability and residual stability, indicating that the material has good deformation resistance and water stability; and is better than Example 1, indicating that the replacement of construction solid waste has a positive effect on the high temperature stability and water stability of the ATB-30 base. At the same time, although the tensile strain at break, splitting tensile strength and fatigue life are lower than those in Example 1, they are still within an acceptable range. This is an embodiment that balances deformation resistance and crack resistance and can meet the requirements of practical applications.
[0052] in, Figure 2 A schematic diagram of a rutting test of an asphalt mixture test block prepared in Example 4 of the present invention; Figure 3 Schematic diagram of the Marshall test of immersion of asphalt mixture test block prepared in Example 4 of the present invention; Figure 4 It is a schematic cross-sectional view of a low-temperature splitting experiment of an asphalt mixture test block prepared in Example 4 of the present invention; Figure 5 Schematic diagram of a three-point bending fatigue test of an asphalt mixture specimen prepared in Example 4 of the present invention.
[0053] As can be seen from the above, this solution makes full use of the characteristics of low price and certain strength of construction solid waste materials, and obtains economical and practical flexible base materials through its unique physical and chemical properties. The flexible base material provided by this solution solves the problem of the accumulation of a large amount of construction solid waste, makes full use of the rich resources in construction solid waste, and has a simple preparation process, high production efficiency, simple and stable operation, convenient control, and easy automation. At the same time, it has been verified through experiments that this flexible base material shows good stability under high temperature and water environment. The durability of the material has been significantly improved, which extends the service life of the road and reduces maintenance costs. In summary, the flexible base material of the present invention not only has significant advantages in economy and environmental protection, but also can meet the needs of modern road construction in terms of performance. It is an ideal choice of road base material.
[0054] The above descriptions are only some embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Any equivalent device or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. An application of construction solid waste mixed with asphalt crushed stone as a road base material, characterized in that: The road base material includes components in parts by weight:
2. The use of construction solid waste mixed with asphalt crushed stone as a road base material as claimed in claim 1, characterized in that: The limestone aggregate has a particle size of less than 37.5 mm.
3. The use of construction solid waste mixed with asphalt crushed stone as a road base material as claimed in claim 1, characterized in that: The construction solid waste includes recycled concrete aggregate and recycled concrete powder. The particle size of the recycled concrete aggregate is 5-20 mm. The recycled construction powder is obtained by grinding the construction materials, drying the moisture in an oven and sieving through a 0.075 mm sieve.
4. The use of construction solid waste mixed with asphalt macadam as claimed in any one of claims 1 to 3 as a road base material, characterized in that: The road base material includes components in parts by weight:
5. The use of construction solid waste mixed with asphalt crushed stone as a road base material as claimed in claim 4, characterized in that: The limestone aggregate includes 19.20 parts of aggregate with a nominal particle size of 0-3 mm; 10.57 parts of aggregate with a nominal particle size of 3-5 mm; 5.00 parts of aggregate with a nominal particle size of 5-10 mm; 6.91 parts of aggregate with a nominal particle size of 10-20 mm; and 34.63 parts of aggregate with a nominal particle size of 20-37.5 mm. The construction solid waste includes 7.51 parts of aggregate with a nominal particle size of 5-10 mm; 10.36 parts of 10-20mm aggregate.
6. A method for preparing construction solid waste mixed with asphalt crushed stone as a road base material, which is used to prepare the road base material in the application of any one of claims 1 to 5, characterized in that: It includes: Weigh each raw material according to the weight ratio of the pavement base material, and then place it in an oven at 105℃±5℃ for 4-6h; Place limestone aggregate and coarse and fine aggregate of construction solid waste in a mixer and mix them properly with a shovel, then add 70# base asphalt and mix for 1-1.5 minutes; Then the mixing was stopped, and the mineral powder and molybdenum mineral powder were added and continued to be mixed until uniform. The total mixing time was 3 minutes to obtain the asphalt mixture. The mixed asphalt mixture is poured into a heated mold for molding to obtain the pavement base material.
Citation Information
Patent Citations
Asphalt mixture taking regenerative micro powder of waste concrete as filler
CN101624273A
Asphalt concrete used for highway engineering and preparation method of asphalt concrete
CN110342857A
Asphalt mortar doped with regenerated micro powder and novel warm mixing agent and preparation method of asphalt mortar
CN115849767A
The asphalt concrete manufacture method of having usedreproduction aggregate and this using reproductionaggregate and waste cement
KR1020050115358A